Design and Validity of Physics Teaching Materials Based on Cognitive Conflict Integrated Virtual Laboratory in Atomic Nucleus - Tisa Febri Delvia; Fatni Mufit; Mugni Bustari (Universitas Negeri Padang, 2021)
Curiculum.2013 requires.the students to be able to improve.the understanding of a.concepts. But it stil not realizet One of the solutions of this problem is to make physics teaching.materials based on cognitive conflicts on atomic nucleus to improve students’ conceptual understanding. The purpose.of this a research is to produce a valid cognitive conflict-based teaching material design. The type of research is Design / Development Research usingn the Plomp model. However, this research is limited to theaPreliminary.Research and Prototype.Phase. The first step is Preliminary Research by analyzing needs and context by conducting journal analysis and interviews with physics teachers in schools. The second step of the Prototype.Phase is the development stage by making the design of teaching materials, conducting validation by researchers (self evaluation) and experts review. From the results.of.the Preliminary Research stage, it was found that in the atomic nucleus theory there were still many misconceptions, there were no teaching materials that integrated models and there was a lack of guidelines for conducting virtual laboratory. In the Prototype Phase, it was found that the results ofathe design of teaching materials is based on cognitive conflict that were developed had passed the self-validation and experts validation tests with a very valid validity level with an averaga value of 0.87. With the acquisition of this value, the design of physics teaching materials based on cognitive conflict is declaredjfeasible.to be used in the learning processin order to improve the conceptual understandingof the students.